Pottery Workshops at Fanum Martis (Northern France): Analysis of pottery production and consumption - Willems, Sonja; Borgers, Barbara (Rei Cretariae Romanae Fautorum Acta, 2017)
This article is an introduction to a wider and integrated approach to potters’ techniques in the southern part of the civitas nerviorum. More precisely, it focuses on the Roman pottery production at the site of Famars, Valenciennes, where recently extensive excavations have yielded ten new pottery kilns, in addition to five known structures. The analysis of the Roman pottery production at Famars is part of a wider research framework in the south of the Nervian territory, which compares the local pottery production at Famars with other regional production sites at Bavay, Pont-sur-Sambre, Sains-du-Nord and the Cambrai region. In this research, an integrated approach is being adopted, using macroscopic, microscopic and chemical analyses, for the identification of potters’ techniques, their movement or transfer of knowledge. A detailed article on the kiln structures and the methods used to analyse potters’ techniques and choices will be published elsewhere in more detail. This article mainly focuses on the context of the Roman pottery production at Famars, and touches upon some of the themes that are being developed in depth in the post-excavation research and the wider research framework.